Kegiatan Webinar Ramadhan dalam Meningkatkan Fokus dan Disiplin Diri melalui Manajemen Waktu - Fauzan Fitra Ramadhan (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to improve participants' understanding of time management in building focus and self-discipline, particularly during the holy month of Ramadan, which is synonymous with various religious and social activities. The activity took place online on March 8, 2026, via Google Meet, with 15 participants, including students and the general public. The activity involved an educational webinar discussing the basic concepts of time management, strategies for managing activities during Ramadan, and the importance of developing disciplined habits in carrying out daily activities. The service method used in this activity was the Asset-Based Community Development (ABCD) approach, emphasizing the utilization of participants' potential and abilities to develop effective time management skills. The activity began with preparation, including creating a webinar flyer, preparing presentation materials using Canva, and scheduling activities through Google Meet. The results showed that participants gained a better understanding of the importance of time management in improving study focus, self-discipline, and productivity during Ramadan. Through this activity, participants are expected to be able to consistently implement time management principles in their daily lives, thereby improving their quality of life both academically and spiritually.